Study of the peculiarities of the transformation of the ground cover of Srivashshya by under the influence of natural and anthropogenic factors (on the example of the Novotroitsky region and the Azov-Syvash National Natural Park) - Polova, I.; Fokina, S. (Land Management, Cadastre and Land Monitoring, 2019)
The article deals with the peculiarities of the transformation of the Prisivashshya soil on the example of a comparative analysis of soil transformation in the Novotroitsky region and the Azov-Sivash National Natural Park under the influence of natural and anthropogenic factors. Soils of the Northern Prisivashia, namely the Novotroitsky area, undergo significant transformations caused by human activity, quickly lose their positive properties in the case of inappropriate agricultural use. Long-term use of soils in arable land and, in particular, their reclamation (ameliorative plowing, irrigation by waters of different quality) cause the existence of soil processes that are different from those existing in the natural environment and are currently under-studied. In modern conditions of land use exact information on the qualitative state of saline soils is necessary for monitoring and rational agricultural use, in connection with which the research issues acquire special scientific and practical significance. On the basis of the comparative analysis, the differences between soils of agricultural use and the soils that are in the natural state within the protected areas are determined. It is proved that the soils of the protected area in comparison with the soil cover of the Novotroitsky district will not undergo significant anthropogenic influence. The territory of the Novotroitsky district is characterized by large scale devastation of agricultural land. Key words: Azov-Syvash national natural park, soil cover, agro-transformed soils, reclamation, natural and anthropogenic factors.